Avena sativa AGG 700775 OATS ... - GLIS Of The ITPGRFA (Australian Grains Genebank, DEECA, 2023)
Plant Genetic Resource. Taxonomy: Avena sativa Common name(s): Oat Other names: NAKOTA Conserved by: Australian Grains Genebank, DEECA (AGG), Australia Local sample unique identifier: AGG 700775 OATS Method of creation: Acquisition Date: 1986-01-01 Other identifiers: n/a,Q2872, n/a,QHO-149 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...